Methods of Expressing Liking Through the Media [on the Example of Facebook.com] - Chudzik, Anna (Poznańskie Studia Slawistyczne, 2015)
The main theme of the article centers on the methods of expressing liking which is understood as a positive attitude towards another person functioning in the Internet. The aim of the paper is to show and discuss elements of communication and language pragmatics typical for emotive speech, including the elements which are results of the new media. The theoretical part concerns two aspects: 1) definition of the emotive (expressive) function In linguistics and of the terms describing phenomena which are related to the science of communication; 2) the Internet as a new tool and an environment for social communication. The analysis is conducted on the written data produced by the Facebook community. Conclusions concern the observed patterns of form, intentional content and functions of written production expressing liking.